Nate the great. - Sharmat, Marjorie Weinman; Simont, Marc (New York, Coward, McCann & Geoghegan, 1972)
Nate the Great solves the mystery of the missing picture.
Children's Catalog (Wilson)
Booklist
School Library Journal
2.0
K-3
Keywords: Mystery and detective stories; Mystery and detective stories